Elevated Thyroglobulin Antibody Level is Associated with Decreased Anti-Müllerian Hormone in Women of Reproductive Age - Jazyra Zynat; Xinling Wang; Li Han; Shuqing Xing; Guzailinuer Jvlaiti; Qingqing Liu; Lingling Dong; Yanying Guo (International Journal of Endocrinology)
Purpose. Women with Hashimoto’s thyroiditis (HT) have an increased risk of ovarian insufficiency. However, whether thyroid antibodies affect the ovarian reserve remains controversial. The aim of this study was to explore the possible relationship between anti-Müllerian hormone (AMH) and thyroid peroxidase antibody (TPOAb) and thyroglobulin antibody (TgAb) levels in women of reproductive age. Methods. A total of 483 women between 18 and 45 years old who had their TPOAb, TgAb, thyroid-stimulating hormone (TSH), free thyroxine (FT4), and AMH levels measured on the same day were enrolled in this study. The levels of TSH, FT4, TPOAb, and TgAb, the prevalence of overt and subclinical hypothyroidism, and the positive rate of TPOAb and TgAb were compared between patients with low (below the 10th percentile), normal (10th to 90th percentile), and high (higher than the 90th percentile) AMH levels. Results. The median AMH level was 1.72 (0.33–4.27) ng/mL. A total of 9.9% of patients had low AMH levels. The TgAb levels and the prevalence of TgAb positivity were higher in the low AMH group (37.62 (13.10–232.68) IU/mL, 35.42%) than in the normal (12.46 (10.0–67.04) IU/mL, 19.59%) and high (13.61 (10.0–95.74) IU/mL, 23.4%) AMH groups (p=0.001, p=0.040, respectively). Serum AMH levels were inversely correlated with TgAb levels (r = −0.114, p=0.013). Conclusion. The AMH of women of reproductive age is affected by HT. Furthermore, women with the lowest AMH level had higher levels of TgAb and a positive rate of TgAb, and high TgAb levels may cause autoimmune damage to the ovaries.